Elaboration, validation and reliability of the safety protocol for pediatric thirst management - Isadora Pierotti; Leonel Alves do Nascimento; Edilaine Giovanini Rossetto; Rejane Kiyomi Furuya; Lígia Fahl Fonseca (Universidade de São Paulo, 2020)
Objective: to elaborate, validate and evaluate the reliability of the Safety Protocol for Pediatric Thirst Management in the immediate postoperative period. Method: methodological quantitative research, based on the assumptions on measurement instrument development. The protocol was elaborated after literature review, interview with specialists and observation of the child's anesthetic recovery. The judges performed theoretical validation through apparent, semantic and content analysis. Content Validity Index was calculated for content validation, whose minimum established concordance was 0.80. Protocol's reliability was evaluated in children between three and 12 years old in the Post Anesthesia Care Unit. Results: in its final version, the protocol consisted of five evaluation criteria: level of consciousness, movement, airway protection, breathing pattern and nausea and vomiting. It presented easy comprehension and relevant content, and all indexes exceeded the minimum agreement of 0.80. Pairs of nurses applied the protocol 116 times to 58 children, resulting in a high reliability index (kappa general = 0.98) Conclusion: the unprecedented protocol developed is valid and is a useful tool for use in anesthetic recovery, aiming to assess safety for reducing the thirst of infant patients.